O professor de língua portuguesa e as imagens de si - município de Monte Alegre de Sergipe - Aragão, Carlos Alexandre Nascimento (2012)
The language teaching has been the subject of discussion in the scientific world for many years, as the approach adopted by teachers is still based on a traditional view of education, more precisely, in the teaching of Grammar Rule. That teaching method has caused a large quantity of withdrawal by the student within the public school, mainly due to the structural repetition of exercises, so that the learner does not perceive the language as a dynamic, historical and dialogical. Consequently, this practice excludes the subject of the processes of verbal interaction. In this context we present research studies related to this work. We work with the theories of Pêcheux (1988), Soares (2001), Guimarães (2005), Barros (2008), Foucault (2008, 2009), Orlandi (1984, 2007, 2009), Mendonça (2009), from which we construct the discussions on the subject. First, we address the process of transmitting knowledge in school, whose legacy is socially approved, revealing the different ways of conceiving the discipline in this pedagogical space, through the control mechanisms mentioned by Foucault (2009). Besides these aspects, we conducted a brief discussion of the pedagogical discourse, present in the school, because we believe that the teacher, who is authorized by the school to create awareness, brings with him a discourse of truth permeated institutionally. However, affected by the forgetting of nº 1, the subject imagines himself as the author of this discourse. Thus, we introduce the postulates of interdiscourse, intradiscourse, forgetting nº 1 and nº 2 (PÊCHEUX, 1988). Then we made a brief historical review of the institution of grammar at school (from Greece to the twentieth century) to understand the overvaluation of the norm in everyday subjects investigated. We also realize a brief summary of the process of establishing the LP in Brazil. By understanding that language is plurivocal, we brought the studies of Bakhtin (2003, 2009), with regard to the enunciation. We also made an approach to the Ethos notion postulated by Maingueneau (1997, 2006, 2008) and Amossy (2008). Finally, we proceeded to a discourse analysis of the teachers‟ speech, based on the postulates discussed. In this context, it is configured as qualitative research, because the discursive analysis of informants' speech.